Efficiency of Pangasius Production in Kota Gajah Subdistrict - Sutarni Sutarni; Dayang Berliana (School of Business, Bogor Agricultural University (SB-IPB), 2019)
The purpose of this study is to analyze the factors that influenced Pangasius production, analyze the economic scale of Pangasius culture business, and analyze the economic efficiency of Pangasius culture business using local feed in the Kota Gajah Subdistrict. The research location is determined intentionally (purposive). The number of samples taken was 41 people. The results showed that: (a) Significant factors affecting Pangasius production in the study area were pool area, initial manufacturer's feed (P1), advanced manufacturer's feed P2, advanced P3 feed, salted fish as local feed ingredients, and fine bran as local feed ingredients, while the number of seeds and non-permanent labor did not significantly influence the production of Pangasius. The business of Pangasius culture in the research area is not yet efficient, both technically and economically. (b) The value of the production elasticity of Pangasius culture in the study area is 1.151, which means the Production Elasticity (EP) is >1, meaning that the economic scale of production of Pangasius culture business is in the condition of increasing return to scale, specifically, the addition of production factors will cause additional output with a larger amount. (c) The use of production factors such as the area of ponds, seeds, factory feed 1, factory feed 2, and factory feed 3 is still possible to be increased so that the profits derived by Pangasius culture business in the study area are optimal. On the other hand, the salted fish variables, fine bran, and labor are not efficient, so the use of these factors of production must be reduced.Keywords: Pangasius, efficiency, production, economical, technical, and local feed